Shaping changes through participatory processes: Local development and renewable energy in rural habitats - Belmonte, Silvina (2015)
The socio-technical adequacy processes of technologies, in general, and particularly, renewable energy, require paradigm changes in the way of thinking and acting in the territory. These processes are key, on post, to achieve greater equality, democratic management, quality of life and environmental sustainability, particularly in the rural areas of Northwest Argentina. The article is based on the premise that these changes are socially constructed. A set of workshops were conducted on purpose to discuss and reach a consensus on conceptual, methodological and practical aspects, associated with the processes of ‘technology transfer’ and rural development. Participation in the workshops focused on technical stakeholders (researchers, technicians and extension workers), identified as links between new technology and the users thereof. From these shared spaces, the conceptual model of socio-technical adequacy was validated and multiple determinants for the processes were identified and prioritized. Finally, consensual action oriented proposals in the following levels: personal-institutional, inter-institutional and public policy. This article concludes that the areas of interaction and collective construction are necessary and feasible for implementation. These areas represent real opportunities to increase equity and improve interventions in rural habitats.